Engineered Porous Carbon for High Volumetric Methane Storage - J. Romanos; S. Sweany; T. Rash; L. Firlej; B. Kuchta; J.C. Idrobo; P. Pfeifer (Adsorption Science & Technology)
This paper covers the optimization of methane volumetric storage capacity by controlling the sub-nanometre (<1 nm) and supra-nanometre (1–5 nm) pore volumes. Nanospace engineering of KOH activated carbon generates an ideal structure for methane storage in which gas molecules are adsorbed as a high-density fluid by strong van der Waals forces into pores that are a few molecules in diameter. High specific surface areas, porosities, sub-nanometre (<1 nm) and supra-nanometre (1–5 nm) pore volumes are quantitatively selected by controlling the degree of carbon consumption and metallic potassium intercalation into the carbon lattice during the activation process. The formation of tuneable sub-nanometre and supra-nanometre pores is validated by sub-critical nitrogen adsorption. Aberration-corrected scanning transmission electron microscopy data show the atomic structure of high-surface-area activated carbon (2600 m 2 /g). While high surface area and high porosity are optimal for gravimetric methane storage, the results indicate that an exclusive sub-nanometre region, a low porosity and an acceptable surface area (approximately 2000 m 2 /g) are ideal for methane volumetric storage, storing 120 g CH 4 /l (184 vol/vol) at 35 bar and room temperature (22 °C). High-pressure methane isotherms up to 150 bar at 30, −25 and −50 °C on optimal activated carbons are presented. Methane volumetric storage capacity at 35 bar reaches 176 g/l (269 vol/vol) and 202 g/l (309 vol/vol) at −25 and −50 °C, respectively.